1970
DOI: 10.4314/jae.v22i1.10s
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Mobile Phone Usage among Cassava Processors in Lafia Local Government Area of Nasarawa State

Abstract: This study investigated the benefits of mobile phone usage among cassava processors in Lafia Local Government Area of Nasarawa State. A simple random sampling technique was used to select 81 cassava processors across four processing centres as respondents. Data collection was by a structured interview schedule. Data analysis was done using descriptive statistics and a linear regression model. The results show that the majority (80.2%) of the respondents were females; the respondents’ mean age was 37 years. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…This implies that, five years of wheat farming experience could give enough experience, if farmers are properly supported with the required extension services, and can facilitate increased knowledge, attitude and participation in wheat farming practices. This is in tandem with Salau, et al (2017), that 65.4% of the respondents had between 6-10 years' experience in farming. About 68.5% male and 43.7% female respondents had access to extension services from JARDA.…”
Section: Socio-economic and Institutional Characteristics Of The Resp...supporting
confidence: 63%
“…This implies that, five years of wheat farming experience could give enough experience, if farmers are properly supported with the required extension services, and can facilitate increased knowledge, attitude and participation in wheat farming practices. This is in tandem with Salau, et al (2017), that 65.4% of the respondents had between 6-10 years' experience in farming. About 68.5% male and 43.7% female respondents had access to extension services from JARDA.…”
Section: Socio-economic and Institutional Characteristics Of The Resp...supporting
confidence: 63%
“…It Mansour Factors Affecting Mobile Phone Usage By Farmers As A Source Of Agricultural Information In Sharqia Governorate, Egypt 422 is natural that the order of these problems varies according to the environment and the context of each study. While Salau et al (2017) saw that the poor coverage of the internet and the high cost of access to the internet were the first of these obstacles, as they were the last obstacles in order according to Khan et al (2019) Other studies such as Abebe and Mammo (2018). About the use of information and communication technology for grain farmers in Ethiopia confirmed that the most important of these problems was the weak mobile network, poor knowledge about using mobile applications, and the high cost of mobile use, while Huda et al (2017) indicated that the poor training on how to browse the Internet and the weak knowledge of how to operate the phone, which were the most important of these obstacles, other studies pointed to the risk of digital illiteracy as a barrier to mobile phone usage (Saroj et al, 2017), while Hoang, (2020) found that the lack of mobile phone knowledge, language barriers, and poor network coverage were the most important of these obstacles.…”
Section: The Most Important Problems Facing the Respondents Regarding...mentioning
confidence: 99%